Gallstone ileus with multiple gallstones: a case report - Sitaula, Deekshanta; Adhikari, Sanjit; Bhattarai, Abhishek (Journal of Chitwan Medical College, 2021)
Gallstone ileus is a rare complication of gallstones and an unusual cause of intestinal obstruction. It typically occurs due to formation of cholecystoduodenal fistula and patients usually present with features of small bowel obstruction. The mainstay of treatment is to relieve the intestinal obstruction with surgical removal of impacting gallstone. Here, we report a case of a male patient presented with features of small bowel obstruction. CT of abdomen demonstrated presence of air in the gallbladder, small bowel obstruction with direct communication of the gallbladder with 1st part of duodenum and multiple calculi in proximal jejunal loops, features suggesting gallstone ileus. The patient underwent exploratory laparotomy and removal of four gallstones via enterotomy. He was discharged after an uneventful postoperative course. The aim of this case report is to report a new unusual case of gallstone ileus and discuss its diagnostic and surgical approaches. Though uncommon, gallstone ileus should always be kept in mind when approaching a case of small bowel obstruction, especially in elderly patients and in patients with known gallstone disease.